1996
DOI: 10.1152/ajpheart.1996.271.3.h1207
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning is not abolished by the delayed rectifier K+ blocker dofetilide

Abstract: ATP-sensitive potassium channels are thought to play an important role in preconditioning. possibly due to shortening of the action potential duration (APD). The purpose of this study was to determine the effect of the class III antiarrhythmic agent dofetilide on preconditioning at a dose that abolishes APD shortening during ischemia A pilot study was performed to find a dose of dofetilide that would abolish the APD shortening effect of preconditioning Anesthetized dogs were subjected to 5-min coronary occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…Similar lack of correlation between the extent of action potential shortening and the reduction of infarct size has also been shown with cromakalim and BMS-180448 [9,10]. Furthermore, Grover et al [11] showed that prevention of action potential shortening by concomitant treatment of dofetilide did not reverse cardioprotective effects of cromakalim. These studies suggested that the opening of the surface KATP channel may not be necessary for the cardioprotection induced in IPC.…”
Section: Introductionmentioning
confidence: 59%
“…Similar lack of correlation between the extent of action potential shortening and the reduction of infarct size has also been shown with cromakalim and BMS-180448 [9,10]. Furthermore, Grover et al [11] showed that prevention of action potential shortening by concomitant treatment of dofetilide did not reverse cardioprotective effects of cromakalim. These studies suggested that the opening of the surface KATP channel may not be necessary for the cardioprotection induced in IPC.…”
Section: Introductionmentioning
confidence: 59%
“…26 I K(ATP) channels are thought to play a role in ischemic preconditioning and, interestingly, indirect reversal of the electromechanical effects of stimulation of I K(ATP) channels by dofetilide does not diminish ischemic preconditioning. 27,28 Dofetilide-induced action potential prolongation is blocked by ␤-adrenergic stimulation. 29 This results from adrenergic enhancement of I Ks , which shortens action potential duration.…”
Section: Effects Of Dofetilide On Action Potential Durationmentioning
confidence: 99%
“…В настоящее время преобладает мнение, что тран-зиторные ишемические атаки являются прежде все-го фактором риска мозгового инсульта. Упоминания об их саногенном эффекте в публикациях последних лет встречаются довольно редко [55][56][57][58][59].…”
Section: Aadsorasunclassified
“…Первоначально ответственными за ИП рассматривались сарколем-мные каналы Katp, активация которых сокращает продолжительность потенциала действия, ингиби-рует поток кальция через каналы L-типа, в резуль-тате чего уменьшается внутриклеточная перегрузка кальцием в процессе ишемии [56,59]. Позднее было установлено, что укорочение потенциала действия активацией сарколемных Katp-каналов не суще-ственно для индуцированной противоишемической защиты миокарда, а при активации митохондри-альных Katp-каналов воспроизводится эффект ИП [56,57]. В последнее время показано, что активация Katp-каналов внутренней митохондриальной мем-браны является не только необходимым, но и до-статочным условием для реализации защитного эффекта гипоксического и ишемического прекон-диционирования [35].…”
Section: Aadsorasunclassified